Smartphone Addiction, Loneliness, Narcissistic Personality, and Family Belonging Among University Students: A Path Analysis - Gokcearslan, Sahin; Yildiz Durak, Hatice; Berikan, Burcu; Saritepeci, Mustafa (Wiley, 2021)
Background The relationship between smartphone addiction (SPA) and loneliness is examined in several studies, however, the mediating effects of the variables related to narcissism and the family on the relationship between SPA and loneliness are not yet available in the literature. Objective The present study investigates the role of SPA on loneliness and the moderating effects of narcissistic personality and family belonging on loneliness. Participants and Setting Data required for research were obtained via an online survey from undergraduate students (n = 500) studying at a public university. Methods In the study, the relationship between the variables was determined by path analysis. Results The results of the path analysis show that there is a significant positive relationship between SPA and loneliness. According to the model, no significant relationship was found between narcissistic personality and family-belonging level. There is a negative and significant mediation effect between SPA and narcissistic personality traits. There is a positive and significant mediation effect between SPA and family belonging. The results of the research are discussed with regard to university students and future directions. Conclusions According to these research results, SPA predicts loneliness. As the level of family belonging decreases, SPA increases. The relationship between university students and their families and environments is among the variables that should be considered when evaluating SPA.
Keywords: Problematic Internet Use; Mobile Phone Addiction; Self-Esteem; Social Anxiety; Chinese Adolescents; College-Students; Parenting Style; Moderating Role; Depression; Prevalence